MO367: Non-Invasive Diagnosis of Vancomycin-Induced Acute Kidney Injury Using Urine Microscopy. (3rd May 2022) - Rafat, Cédric; Zaworski, Jérémy; Doreille, Alice; Frochot, Vincent; Gaudry, Stéphane; Daudon, Michel; Luque, Yosu; Letavernier, Emmanuel
Abstract: BACKGROUND AND AIMS: Vancomycin stands out both as being a potent cause of AKI (V-AKI) and as one of the most universally prescribed antimicrobial drugs. From a pathophysiological standpoint, it was hitherto believed that V-AKI stemmed from the intracellular accumulation of vancomycin in the proximal tubule, which elicits oxidative stress and ultimately translates in cell apoptosis. Recently, a study has shown that vancomycin in the setting of overt drug overdose, can co-precipitate with uromodulin causing microspheric obstructive aggregates in the tubular lumen both in experimental models and in patients [1 ]. Further documentation of this novel mechanism has been hindered by the need to procure kidney tissue so as to perform ad hoc immunostaining. Furthermore, it remains to be proven that the presence of vancomycin microspheres represents a reliable marker for V-AKI. Urine based vancomycin-immunostaining may represent a valuable non-invasive approach. METHOD: The urine of patients presenting with vancomycin overdose determined by plasma trough levels >15 mg/L along with acute kidney injury (according to KDIGO guidelines) were subjected to light microscopic urinalysis. Whenever microscopic urinalysis yielded the presence of casts, immunostaining was performed. Briefly, a pellet of urine was spread on a slide and immunostaining performed with a specific anti-vancomycin antibody (Abbot 6E-4421, 1/1000) prior to repeat microscopic examination. Infrared spectrophotometry was performed to ascertain the nature of the casts by comparing the spectrum to a reference vancomycin spectrum. Patients were deemed to have V-AKI whenever at least one vancomycin positive cast was observed following immunostaining. The urine of control patients was subjected to the same procedure: they were defined as patients exposed to vancomycin with or without vancomycin overdose but with no AKI. RESULTS: A total of 5 patients with vancomycin overdose KDIGO stage 3 AKI were found to exhibit casts with positive vancomycin immunostaining (Fig. 1). On light microscopic urinalysis, vitreous casts devoid of refringence after polarization could be observed in each case. Upon infrared spectrophotometry, the casts displayed a Fourier transform spectrum consistent with vancomycin. In three of the cases, V-AKI was considered the sole or primary cause of AKI. The patient displayed abundant and markedly stained casts upon anti-vancomycin immunostaining (Fig. 1A). Overt and massive vancomycin overdosing was evidenced in all cases. In one case, the patient concurrently received piperacillin-tazobactam and in another case the patient was exposed to iodinated contrast media. The renal function course was favourable with full recovery in all three instances. In two cases, competing causes of AKI were either evidenced or not. In one case, the patient displayed septic shock which indicated vancomycin therapy. In another case, the patient was suspected to have immunoallergic intersititial nephritis. The patients exhibited rare casts with only faint staining (Fig. 1B). In both cases, vancomycin overdose could not be documented. V-AKI was deemed a possible concurrent cause of AKI. None of the 5 control patients yielded casts after light microscopic urinalysis. CONCLUSION: Vancomycin cast detection on urine microscopy is feasible and can be enhanced by a straightforward immunostaining technique and represents a unique opportunity for a non-invasive diagnosis of V-AKI. Further studies are required to refine diagnostic criteria-based urine immunostaining detection. They also needed to determine whether detection of V-AKI merely reflects impaired vancomycin urinary excretion in the setting of AKI or can be regarded as a sensitive and specific marker of vancomycin-induced tubular obstruction and injury.